College level Challenges of E-learning in Bhojpur - Raut, Indra Raj (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2023)
Education system is being upgraded day by day with advance technologies that are from traditional learning to modern E-learning. This article is relevant for learners as it is providing flexibility in learning with optional choices for study to the learners with unlimited access of information. E-learning is the effective tool of teaching and learning process and different schools and universities of Nepal are broadly adopting this E-learning strategy and offering for distance education nowadays. Supporting higher education with modern technologies like E-Learning is very important for a country to improve quality of education, to meet student’s expectations and to continue teaching-learning and training when face to face education is less possible. The main objective of this research is to find out the college level challenges of E-learning in Bhojpur and to show the change of learning process from the traditional learning to E-learning in Bhojpur. This paper is qualitative in nature. The paper has been written in descriptive way. Both primary and secondary sources are used to carry out it. The question-answer method is used to get primary information from the respondents. The researcher has used open ended questions as a tool and asked to the respondents respectively. From this study, we found the college level challenges of E-learning in Bhojpur. The challenges mentioned are lack of ICT infrastructure and facilities, lack of social interaction among students and educators, lack of budget and fund, less focused on online learning, Unwillingness of the learners, poor internet connection, motivation issues, assessment and evaluation process.